2011
DOI: 10.1248/bpb.34.632
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Iron-Uptake Systems by a Mutation of luxS Encoding an Autoinducer-2 Synthase in Vibrio vulnificus

Abstract: Vibrio vulnificus is a Gram-negative halophilic bacterium that causes primary septicemia and necrotizing wound infections with a high mortality rate in susceptible individuals. V. vulnificus possesses a variety of virulence factors, including acid neutralization, capsular polysaccharide expression, iron acquisition, cytotoxicity, motility, and expression of proteins involved in attachment and adhesion. The concerted expression of the virulence factors is likely required for pathogenesis and appears to be under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Moreover, the supplementation of media with (25). Similarly, mutation of luxS in Vibrio vulnificus increased the expression of the vulnibactin receptor but decreased the expression of receptors for aerobactin and heme (28). However, in contrast to the present study, the effect of the luxS mutations on actual cellular iron levels in these organisms was not determined.…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, the supplementation of media with (25). Similarly, mutation of luxS in Vibrio vulnificus increased the expression of the vulnibactin receptor but decreased the expression of receptors for aerobactin and heme (28). However, in contrast to the present study, the effect of the luxS mutations on actual cellular iron levels in these organisms was not determined.…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, Fur is the key repressor that prevents the overexpression of vvsAB in response to Fe in Fe-sufficient environments, whereas SmcR is another key repressor that prevents the overexpression of vvsAB in response to bacterial density in Fe-deficient environments. In another study [69], a mutation in luxS slightly decreased the expression of vuuA but slightly increased the expression of iutA and hupA in V. vulnificus (Figs. 2, 3 and 5).…”
Section: Regulation Of Iuss By Quorum Sensingmentioning
confidence: 91%
“…Under high-iron conditions, Fur repressed vvsA transcription, while in low-iron environments, SmcR regulated the expression of the siderophore biosynthesis genes (245). Using a luxS mutant defective in the synthesis of autoinducer 2 (AI-2), Kim and Shin observed an increase in the synthesis of the siderophore receptors for aerobactin (IutA) and heme (HupA), suggesting that they are also repressed by quorum sensing (246). Additional studies revealed a more complex connection between iron and quorum sensing (247).…”
Section: Other Environmental Sensors and Regulators For Iron Acquisitionmentioning
confidence: 99%